1022. Impact of Hospitalization on Antiretroviral Therapy for People Living with HIV. (31st December 2020) - Ladak, Amber; Young, Henry N; Tang, Emily; Curtis, Jessica; Chastain, Daniel B
Abstract: Background: Persons living with HIV (PLWH) are frequently hospitalized for reasons often unrelated to HIV. Transitioning of antiretroviral therapy (ART) while inpatient may not always be an immediate priority due to lack of knowledge, formulary restrictions, and patient status. This could lead to medication errors and gaps in therapy, which can persist at discharge, and could lead to viral rebound and disease progression. The purpose of this study was to identify effects of hospitalization on ART for PLWH. Methods: This was an IRB approved, multi-center, retrospective cohort study of patients with HIV and/or AIDS based on ICD codes. Patients were included if they were at least 18 years old, receiving outpatient ART prior to admission, and hospitalized between March 2016 and March 2018. Patients were excluded if they were pregnant and only received intravenous zidovudine during their hospitalization. The primary objective was to determine the rate of ART restarted during hospitalization. Secondary objectives included rate at which inpatient ART was modified compared to outpatient regimen, and risk factors associated with regimen modification. Results: Of 400 patients screened, 295 (74%) patients were on an outpatient ART regimen and were included in the study. Approximately half, 51%, were on a single tablet regimen (STR) outpatient. This population was majority male (59%) and of black race (87%). Median age was 49 years. Median CD4 count was 160 cells/mm3, while median HIV RNA for those with detectable viral load was 57, 095 copies/mL. 236 of 295 patients (80%) received ART during their inpatient stay. However, 70 (30%) of these patients received a regimen that differed from their outpatient ART regimen. 69% of regimens were modified for reasons other than to optimize therapy. Patient sex, place of admission, and receipt of a STR or multi-tablet regimen (MTR) as an outpatient did not significantly impact rate of regimen modification. Conclusion: Ensuring appropriate transition of ART during hospitalization remains an area in need of improvement. No one specific factor was associated with whether outpatient ART was appropriately and accurately restarted during hospitalization. Thus, there are many opportunities to improve transitions of care and antiretroviral stewardship. Disclosures: All Authors : No reported disclosures